Federal Crop Insurance and the Disincentive to Adapt to Extreme Heat - Annan, Francis; Schlenker, Wolfram (American Economic Review, 2015)
Despite significant progress in average yields, the sensitivity of corn and soybean yields to extreme heat has remained relatively constant over time. We combine county-level corn and soybeans yields in the United States from 1989-2013 with the fraction of the planting area that is insured under the federal crop insurance program, which expanded greatly over this time period as premium subsidies increased from 20 percent to 60 percent. Insured corn and soybeans are significantly more sensitive to extreme heat that uninsured crops. Insured farmers do not have the incentive to engage in costly adaptation as insurance compensates them for potential losses.